Case report: anti-IL-6 autoantibodies in a patient with immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome - Lorenzini, Tiziana; Malmström, Lars; Sabet, Ola; Milanesi, Samantha; Tintor, Diana; Walser, Severin; Köppen, Julius; Soomann, Maarja; Hauri-Hohl, Mathias; Prader, Seraina; Doffinger, Rainer; Pachlopnik Schmid, Jana (Frontiers in Immunology, 2025)
We describe an atypical presentation of Immune dysregulation, Polyendocrinopathy, Enteropathy, X-linked syndrome. The patient exhibited food allergies and eczema, along with recurrent and severe infections, but notably lacked the hallmark chronic diarrhea and autoimmune polyendocrinopathy. Whole-exome sequencing revealed the hemizygous FOXP3 variant c.210+1G>T resulting in a loss of protein expression. Immunophenotyping showed an unusual overlap between immune deficiency and immune dysregulation. The patient had CD4+ lymphopenia, with a marked reduction of naïve CD4+ T cells, and impaired T cell proliferation to specific antigens. Moreover, he had reduced serum levels of immunoglobulin (Ig) G2, IgA, and IgM, but high IgE levels and eosinophilia. Given these features consistent with a cellular and humoral immune defect predisposing to infections, the patient was treated with immunoglobulin replacement therapy, which was beneficial. We identified an altered immunophenotypic signature shared between T regulatory and T effector cells. This T helper 1-like memory phenotype corresponded to an increased secretion of interferon-γ following ex vivo stimulation of peripheral mononuclear cells. A key immunological finding was the presence of likely neutralizing anti-IL-6 autoantibodies which, to the best of our knowledge, have never been reported in patients with IPEX syndrome. Although documented later in the disease course, the latter might explain the Hyper IgE syndrome-like features displayed by the patient, including the allergic manifestations in the absence of hyperactivation of the T helper 2 compartment, as well as the poor inflammatory response during infections. This case extends our knowledge of IPEX syndrome by: i) expanding the spectrum of clinical presentations; ii) revealing a distinct phenotypic signature affecting both T regulatory and T effector cells; iii) suggesting that autoantibodies against cytokines may play a previously underappreciated role in shaping the disease manifestations, not only by driving immune dysregulation and allergy but also by impairing immune defense against infections.